Carbon dioxide laser vaporization in the treatment of cervical intraepithelial neoplasia (CIN) of grade I and II - Dimitrov, Goran; Panov, Sasho; Stojanovska, Valentina; Milenkova, Snezhana; Basheska, Neli (Macedonian Surgical Association, 2004)
The efficiency of carbon dioxide (CO2) laser vaporization in the treatment of cervical intraepithelial neoplasia (CIN) as an ablative treatment was evaluated in 74 patients of the Colposcopy Outpatient Service of the University Clinic of Gynecology and Obstetrics, Skopje, Macedonia. After proper diagnosis (histological confirmation of CIN) and excluding existence of intracervical lesion, all patients were submitted to CO2 laser vaporization treatment using MARTIN laser type MCO 50 with power of 50W, coupled through micromanipulator to a LEISEGANG colposcope 3DLF with focal distance of 300 mm. The follow-up (colposcopy, cytology and Polymerase Chain Reaction (PCR) testing for human papillomavirus (HPV) infection) showed high success rates of laser treatment of CIN (low persistence or recurrence rates of CIN - 8.4% and satisfactory HPV clearance rate - 81% in patients with previously diagnosed HPV infection, after at least 6 months following the intervention). Our results as well as those of other studies support the conclusion that CO2 laser vaporization is a highly effective treatment modality for patients with CIN.
Јаглероднодиоксидна ласер вапоризација во третманот на цервикалната интраепителна неоплазма (CIN) од I и II степен
Keywords: carbon dioxide laser surgery; vaporization; cervical intraepithelial neoplasia; human papillomavirus